Causes and risk profiles of mortality among individuals with nonalcoholic fatty liver disease - Konyn, Peter; Ahmed, Aijaz; Kim, Donghee (Clinical and molecular hepatology, 2023)
Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in the United States and worldwide. Though nonalcoholic fatty liver per se may not be independently associated with an increased risk for all-cause mortality, it is associated with a number of harmful metabolic risk factors, such as type 2 diabetes mellitus, hyperlipidemia, obesity, a sedentary lifestyle, and an unhealthy diet. The fibrosis stage is a predictor of all-cause mortality in NAFLD. Mortality in individuals with NAFLD has been steadily increasing, and the most common cause-specific mortality for NAFLD is cardiovascular disease, followed by extra-hepatic cancer, liver-related mortality, and diabetes. High-risk profiles for mortality in NAFLD include PNPLA3 I148M polymorphism, low thyroid function and hypothyroidism, and sarcopenia. Achieving weight loss through adherence to a high-quality diet and sufficient physical activity is the most important predictor of improvement in NAFLD severity and the benefit of survival. Given the increasing health burden of NAFLD, future studies with more long-term mortality data may demonstrate an independent association between NAFLD and mortality.